Chlorine-powder-free rubber treating agent for shoe making industry and preparation method of chlorine-powder-free rubber treating agent

By combining components such as silane-modified EVA emulsion and lanthanum oxide/cerium oxide composite powder, a dynamic water and oxygen trapping layer and a whisker/plate composite structure are constructed, which solves the problem of insufficient resistance to humid heat and high temperature stability of chlorine-free rubber treatment agents in the footwear industry, and achieves efficient interfacial bonding and improved high temperature stability.

CN120888252APending Publication Date: 2025-11-04NANPAO RESINS (FOSHAN) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511157862.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

Existing chlorine-free rubber treatment agents have problems with insufficient resistance to damp heat and high temperature stability in the footwear industry. In particular, they are prone to phase separation under high temperature and high pressure, which leads to a decrease in interfacial bonding force. They also have weak adhesion to non-polar rubber or oily surfaces, thus limiting their applicability.

Method used

By employing components such as silane-modified EVA emulsion, lanthanum oxide/cerium oxide composite powder, stearic acid-modified calcium sulfate whiskers, and silane-modified flake talc powder, a dynamic water and oxygen trapping layer and a whisker/flake composite structure are formed through plasma activation and chemical cross-linking, thereby improving interfacial bonding and high-temperature stability.

Benefits of technology

It significantly improves the hygrothermal resistance and high-temperature stability of rubber treatment agents, enhances interfacial bonding and impact toughness, reduces overall costs, and is suitable for existing spraying equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a chlorine-powder-free rubber treatment agent for shoe making industry and a preparation method thereof, and belongs to the technical field of rubber treatment agents. The coating is prepared from the following components in parts by weight: 35 to 45 parts of silane modified EVA (Ethylene Vinyl Acetate) emulsion, 15 to 20 parts of acrylate emulsion, 5 to 8 parts of lanthanum oxide / cerium oxide composite powder, 2 to 3 parts of zinc borate, 6 to 8 parts of pretreated calcium sulfate whisker, 4 to 6 parts of silane modified flake talcum powder, 3 to 5 parts of epoxy siloxane curing agent, 1 to 2 parts of zirconium acetylacetonate, 0.5 to 1 part of nonionic wetting agent, 0.3 to 0.5 part of defoaming agent and 0.4 to 0.6 part of flatting agent. The combined stearic acid modified calcium sulfate whisker and KH550 coupled talcum powder are adopted to construct a whisker / sheet-shaped dual composite structure; water vapor is blocked while the high-temperature stability is improved; the lanthanum oxide / cerium oxide composite rare earth blocks the damp-heat aging effect due to the high electronegativity of lanthanum and the variable valence characteristic of cerium, and the service life of the product is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of rubber treatment agent technology, specifically relating to a chlorine-free rubber treatment agent for the footwear industry and its preparation method. Background Technology

[0002] The traditional footwear industry widely uses neoprene adhesives, which contain chlorides that may release chlorinated organic compounds during processing and use, exhibiting environmental persistence, bioaccumulation, and toxicity. The adhesion of chlorine-free adhesives to rubber substrates relies on complex surface treatment processes, but traditional chlorination processes themselves carry the risk of chlorine residue. Eliminating chlorine treatment requires formula optimization to compensate for the loss of interfacial bonding strength. Vulcanization and injection molding processes have stringent requirements for the thermal stability of treatment agents; existing chlorine-free formulations are prone to phase separation under high temperature and pressure, leading to delamination at the rubber-sole interface.

[0003] Patent application CN 119978938 A discloses a two-component rubber treatment agent for yellowing resistance without sanding and its application method. The first component consists of 40-60 parts by weight of modified chloroprene rubber latex, 5-10 parts of coupling agent, 2-5 parts of antioxidant, 3-6 parts of light stabilizer, 2-4 parts of defoamer, and 3-6 parts of dispersant. The second component is either organosilicon-modified nano-alumina-modified silica powder or organosilicon-modified nano-silica powder. The treatment agent employs a triple protection mechanism: the modified chloroprene latex (GMA grafted) is inherently resistant to aging; the antioxidant (hindered phenol + thioester composite) inhibits free radical oxidation; and the light stabilizer (hindered amine) shields against ultraviolet rays, thus optimizing the yellowing resistance. However, the risk of chlorine residue has not been completely resolved. Modified chloroprene latex itself contains chlorine, and long-term use may still release chlorides, leading to potential yellowing, as well as insufficient low-temperature and oil resistance. Chloroprene latex is prone to crystallization in low-temperature environments, resulting in film cracking. It also has weak adhesion to non-polar rubber or oily surfaces, limiting its applicability.

[0004] Existing chlorine-free technologies have limitations in the application of rubber treatment agents in the footwear industry. Existing chlorine-free formulations lack sufficient introduction of polar groups and are susceptible to hydrolysis due to humid and hot environments, resulting in an interfacial bond strength attenuation rate of over 50%. Vulcanization and injection molding processes require the treatment agent to remain stable at 120-180℃, but existing chlorine-free formulations (such as waterborne acrylic resins) lack the rigid structural support of chlorine-based materials, leading to intensified molecular chain segment movement and phase separation at high temperatures. Furthermore, chlorine-free systems (such as UV-cured resins) rely on specific energy inputs (such as UV light irradiation) and have poor compatibility with traditional hot-pressing processes in footwear manufacturing. Summary of the Invention

[0005] The purpose of this invention is to provide a chlorine-free rubber treatment agent for the footwear industry and its preparation method, so as to improve the chlorine-free rubber treatment agent's resistance to damp heat and high temperature stability.

[0006] The objective of this invention can be achieved through the following technical solutions: A chlorine-free rubber treatment agent for footwear manufacturing, comprising, by weight, 35-45 parts silane-modified EVA emulsion, 15-20 parts acrylate emulsion, 5-8 parts lanthanum oxide / cerium oxide composite powder, 2-3 parts zinc borate, 6-8 parts pretreated calcium sulfate whiskers, 4-6 parts silane-modified flake talc, 3-5 parts epoxy siloxane curing agent, 1-2 parts zirconium acetylacetonate, 0.5-1 part nonionic wetting agent, 0.3-0.5 parts defoamer, and 0.4-0.6 parts leveling agent.

[0007] Furthermore, the silane-modified EVA emulsion is prepared by the following steps: Preheat the EVA emulsion to 55-60℃, add KH570 (γ-methacryloyloxypropyltrimethoxysilane), and react for 2-2.5 hours to form a silane-modified EVA emulsion.

[0008] Furthermore, the weight ratio of the EVA emulsion to KH570 is (94-96):(4-6); the content of ethylene vinyl acetate in the EVA emulsion is 28% to 33%.

[0009] Silane-modified EVA emulsion is a matrix resin with pre-placed siloxane crosslinking points. During later curing, it forms a Si-O-Si network, which can improve the water resistance of the coating.

[0010] Furthermore, the acrylate copolymer emulsion is a core-shell structured emulsion, with the core layer being methyl methacrylate-styrene copolymer and the shell layer being butyl acrylate-acrylic acid copolymer.

[0011] Furthermore, the lanthanum oxide / cerium oxide composite powder is prepared by the following steps: Lanthanum oxide and cerium oxide were ball-milled and mixed, and then subjected to plasma activation treatment to obtain lanthanum oxide / cerium oxide composite powder.

[0012] Furthermore, the weight ratio of lanthanum oxide to cerium oxide is 1:(0.9-1.1); the plasma activation treatment conditions are an inert gas atmosphere, 290-300W, and 10-12 minutes.

[0013] Furthermore, the pretreated calcium sulfate whiskers are obtained by the following steps: Calcium sulfate whiskers are dried in an oven at 100-110℃ for 2-2.5 hours, dissolved in an ethanol aqueous solution with stearic acid, stirred in a water bath at 55-60℃ until completely dissolved, filtered, heated to 88-92℃, stirred for 30-40 minutes, washed 2-3 times with hot water at 55-60℃, and dried with hot air at 105-110℃ for 1-1.5 hours to obtain pretreated calcium sulfate whiskers.

[0014] Furthermore, the weight ratio of the calcium sulfate whiskers to stearic acid is 100:(1.8-2.5).

[0015] Furthermore, the silane in the silane-modified flake talc powder is one or a combination of KH550, KH560 and KH570.

[0016] A method for preparing a chlorine-free rubber treatment agent for the footwear industry includes the following steps: S1. Lanthanum oxide / cerium oxide composite powder, zinc borate, silane coupling agent and deionized water are dispersed and ground to prepare rare earth slurry; S2. Slowly add zirconium acetylacetonate to silane-modified EVA emulsion and acrylate emulsion, stir, heat and react, add nonionic wetting agent to obtain polymer system; S3. Slowly add the rare earth slurry to the polymer system, stir, and then add pretreated calcium sulfate whiskers and silane-modified flaky talc in sequence. Emulsify to form a uniform composite. S4. After cooling to 32-35℃, add epoxy siloxane curing agent, and simultaneously add defoamer and leveling agent while stirring at low speed; defoam and cure, filter and discharge to obtain chlorine-free rubber treatment agent for the footwear industry.

[0017] Furthermore, the dispersion and grinding conditions in S1 are stirring at 2800-3000 rpm for 15-20 minutes.

[0018] Furthermore, in the S2 process, the temperature is raised to 45-50°C and reacted for 30-35 minutes with a stirring speed of 400-450 rpm.

[0019] Furthermore, the emulsification conditions in S3 are: 45-50°C, treated at 9000-10000 rpm for 5-7 minutes.

[0020] Furthermore, in step S4, the degassing and ripening process involves transferring the material to a vacuum reactor (-0.08 MPa) for degassing for 20-25 minutes and then ripening it at 37-40°C for 22-24 hours. The filter screen has a pore size of 180-220 mesh.

[0021] Furthermore, the nonionic wetting agent is Tego Wet 270; the epoxy siloxane curing agent is Silquest A-187; the defoamer is BYK-024; and the leveling agent is Tego Glide 410.

[0022] The beneficial effects of this invention are: (1) This invention replaces chlorine-containing accelerators with lanthanum oxide / cerium oxide composite rare earth elements, utilizing the high electronegativity of rare earth elements (lanthanum has high electronegativity) and the variable valence characteristics of cerium ( A dynamic water and oxygen trapping layer is formed at the coating interface: it adsorbs water molecules and catalytically decomposes them into ·OH free radicals. It is reduced to H2O, which blocks the effects of damp heat aging, provides long-lasting corrosion protection, completely eliminates metal corrosion caused by chloride ion migration, and extends product life.

[0023] (2) The present invention uses a combination of stearic acid modified calcium sulfate whiskers and KH550 coupled talc powder to construct a whisker / plate dual composite structure; on the one hand, the whisker skeleton inhibits polymer melting flow at high temperature and has excellent high temperature dimensional stability; on the other hand, the directional arrangement of plate talc powder extends the water molecule penetration path and blocks water vapor; and the whisker bridging cracks greatly improves the impact toughness of the treatment agent.

[0024] (3) The present invention uses γ-siloxane-grafted EVA emulsion as the matrix, and through low-temperature condensation crosslinking, the silane side chain migrates to the interface to reduce surface energy, shorten the leveling time, and optimize the high-temperature film-forming properties: acetylacetone zirconium catalyzes the reaction between silane and rubber hydroxyl groups to improve peel strength; in addition, the prepared treatment agent is an aqueous system with low VOC, which can be directly used in existing spraying equipment to reduce overall costs. Detailed Implementation

[0025] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.

[0026] Example 1 This embodiment provides a chlorine-free rubber treatment agent for the footwear industry, which is prepared through the following steps: S1. Preheat 95 parts of EVA emulsion (ethylene vinyl acetate content 30%) to 60°C, add 5 parts of KH570, and react for 2 hours to form silane-modified EVA emulsion. 20 parts of lanthanum oxide and 20 parts of cerium oxide were ball-milled and mixed, and then subjected to plasma activation treatment (inert gas atmosphere, 300W, 10 minutes) to obtain lanthanum oxide / cerium oxide composite powder; 100 parts of calcium sulfate whiskers were dried in an oven at 110°C for 2 hours, and then dissolved in an ethanol aqueous solution with 2.0 parts of stearic acid. The mixture was stirred in a water bath at 60°C until completely dissolved, filtered, heated to 90°C, stirred for 30 minutes, washed twice with hot water at 60°C, and dried with hot air at 110°C for 1 hour to obtain pretreated calcium sulfate whiskers. S2. Add 6 parts of lanthanum oxide / cerium oxide composite powder, 2.5 parts of zinc borate and 0.8 parts of silane coupling agent KH560 to a high-speed disperser, add 30 parts of deionized water, disperse at 3000 rpm for 15 minutes, and grind through a basket mill to prepare rare earth slurry. S3. Add 40 parts of silane-modified EVA emulsion and 18 parts of acrylate emulsion to the reactor in sequence, slowly add 1.5 parts of zirconium acetylacetonate, stir at 400 rpm, heat to 50°C and react for 30 minutes, add nonionic wetting agent Tego Wet270 to obtain polymer system. S4. Slowly add the rare earth slurry to the polymer system, stirring at 1200 rpm for 20 minutes. Then add 7 parts of pretreated calcium sulfate whiskers and 5 parts of silane (KH550) modified flaky talc powder in sequence. Process the mixture for 5 minutes using a high-shear emulsifier (10000 rpm) to form a uniform composite. S5. After cooling to 35℃, add 4 parts of epoxy siloxane curing agent (Momentive Silquest A-187), 0.4 parts of defoamer (BYK-024) and 0.5 parts of leveling agent (Tego Glide 410) simultaneously, and stir at low speed of 500rpm for 30 minutes; transfer to a vacuum reactor (-0.08MPa) for degassing for 20 minutes, and cure at 40℃ for 24 hours. Filter the material (using a 200-mesh filter) to obtain a chlorine-free rubber treatment agent for the footwear industry.

[0027] Example 2 The difference between this embodiment and embodiment 1 is that the processing conditions in S2-S5 are adjusted. The specific implementation of S2-S5 is as follows: S2. Add 6 parts of lanthanum oxide / cerium oxide composite powder, 2.5 parts of zinc borate and 0.8 parts of silane coupling agent KH560 to a high-speed disperser, add 30 parts of deionized water, disperse at 2900 rpm for 18 minutes, and grind through a basket mill to prepare rare earth slurry. S3. Add 40 parts of silane-modified EVA emulsion and 18 parts of acrylate emulsion to the reactor in sequence, slowly add 1.5 parts of zirconium acetylacetonate, stir at 450 rpm, heat to 48°C and react for 35 minutes, add nonionic wetting agent Tego Wet270 to obtain polymer system. S4. Slowly add the rare earth slurry to the polymer system, stirring at 1200 rpm for 20 minutes. Then add 7 parts of pretreated calcium sulfate whiskers and 5 parts of silane (KH550) modified flake talc powder in sequence. Use a high-shear emulsifier (9500 rpm) at 50°C for 6 minutes to form a uniform composite. S5. After cooling to 35℃, add 4 parts of epoxy siloxane curing agent (Momentive Silquest A-187), 0.4 parts of defoamer (BYK-024) and 0.5 parts of leveling agent (Tego Glide 410) simultaneously, and stir at low speed of 500rpm for 30 minutes; transfer to a vacuum reactor (-0.08MPa) for degassing for 25 minutes, and cure at 40℃ for 24 hours. Filter the material (using a 200-mesh filter) to obtain a chlorine-free rubber treatment agent for the footwear industry.

[0028] The remaining raw materials and preparation process are the same as in Example 1.

[0029] Example 3 The difference between this embodiment and embodiment 1 is that the processing conditions in S2-S5 are adjusted. The specific implementation of S2-S5 is as follows: S2. Add 6 parts of lanthanum oxide / cerium oxide composite powder, 2.5 parts of zinc borate and 0.8 parts of silane coupling agent KH560 to a high-speed disperser, add 30 parts of deionized water, disperse at 2800 rpm for 20 minutes, and grind through a basket mill to prepare rare earth slurry. S3. Add 40 parts of silane-modified EVA emulsion and 18 parts of acrylate emulsion to the reactor in sequence, slowly add 1.5 parts of zirconium acetylacetonate, stir at 450 rpm, heat to 45°C and react for 30 minutes, add nonionic wetting agent Tego Wet270 to obtain polymer system. S4. Slowly add the rare earth slurry to the polymer system, stirring at 1200 rpm for 20 minutes. Then add 7 parts of pretreated calcium sulfate whiskers and 5 parts of silane (KH560) modified flake talc powder in sequence. Treat the mixture at 50°C for 5 minutes using a high-shear emulsifier (10000 rpm) to form a uniform composite. S5. After cooling to 33℃, add 4 parts of epoxy siloxane curing agent (Momentive Silquest A-187), 0.4 parts of defoamer (BYK-024) and 0.5 parts of leveling agent (Tego Glide 410) simultaneously, and stir at low speed of 500rpm for 30 minutes; transfer to a vacuum reactor (-0.08MPa) for degassing for 20 minutes, and cure at 38℃ for 24 hours. Filter the material (using a 200-mesh filter) to obtain a chlorine-free rubber treatment agent for the footwear industry.

[0030] The remaining raw materials and preparation process are the same as in Example 1.

[0031] Example 4 The difference between this embodiment and Embodiment 1 is that the amount of stearic acid is increased. The specific implementation method of S1 is as follows: S1. Preheat 95 parts of EVA emulsion (ethylene vinyl acetate content 30%) to 60°C, add 5 parts of KH570, and react for 2 hours to form silane-modified EVA emulsion. 20 parts of lanthanum oxide and 20 parts of cerium oxide were ball-milled and mixed, and then subjected to plasma activation treatment (inert gas atmosphere, 300W, 10 minutes) to obtain lanthanum oxide / cerium oxide composite powder; 100 parts of calcium sulfate whiskers were dried in an oven at 110°C for 2 hours, and then dissolved in an ethanol aqueous solution with 2.4 parts of stearic acid. The mixture was stirred in a water bath at 60°C until completely dissolved, filtered, heated to 90°C, stirred for 30 minutes, washed twice with hot water at 60°C, and dried with hot air at 110°C for 1 hour to obtain pretreated calcium sulfate whiskers. The remaining raw materials and preparation process are the same as in Example 1.

[0032] Example 5 Compared with Example 1, the difference in this embodiment is that the amount of each component in S2-S5 is adjusted. The specific implementation of S2-S5 is as follows: S2. Add 8 parts of lanthanum oxide / cerium oxide composite powder, 3 parts of zinc borate and 0.8 parts of silane coupling agent KH560 to a high-speed disperser, add 30 parts of deionized water, disperse at 3000 rpm for 15 minutes, and grind through a basket mill to make rare earth slurry. S3. Add 45 parts of silane-modified EVA emulsion and 15 parts of acrylate emulsion to the reactor in sequence, slowly add 1.5 parts of zirconium acetylacetonate, stir at 400 rpm, heat to 50°C and react for 30 minutes, add nonionic wetting agent Tego Wet270 to obtain polymer system. S4. Slowly add the rare earth slurry to the polymer system, stirring at 1200 rpm for 20 minutes. Then add 8 parts of pretreated calcium sulfate whiskers and 5 parts of silane (KH570) modified flake talc powder in sequence. Treat the mixture at 50°C for 5 minutes using a high-shear emulsifier (10000 rpm) to form a uniform composite. S5. After cooling to 35℃, add 3 parts of epoxy siloxane curing agent (Momentive Silquest A-187), 0.3 parts of defoamer (BYK-024) and 0.4 parts of leveling agent (Tego Glide 410) simultaneously, and stir at low speed of 500rpm for 30 minutes; transfer to a vacuum reactor (-0.08MPa) for degassing for 20 minutes, and cure at 40℃ for 24 hours. Filter the material (using a 200-mesh filter) to obtain a chlorine-free rubber treatment agent for the footwear industry.

[0033] The remaining raw materials and preparation process are the same as in Example 1.

[0034] Example 6 Compared with Example 1, the difference in this embodiment is that the amount of each component in S2-S5 is adjusted. The specific implementation of S2-S5 is as follows: S2. Add 5 parts of lanthanum oxide / cerium oxide composite powder, 2 parts of zinc borate and 0.8 parts of silane coupling agent KH560 to a high-speed disperser, add 30 parts of deionized water, disperse at 3000 rpm for 15 minutes, and grind through a basket mill to make rare earth slurry. S3. Add 37 parts of silane-modified EVA emulsion and 16 parts of acrylate emulsion to the reactor in sequence, slowly add 1.5 parts of zirconium acetylacetonate, stir at 400 rpm, heat to 50°C and react for 30 minutes, add nonionic wetting agent Tego Wet270 to obtain polymer system. S4. Slowly add the rare earth slurry to the polymer system, stirring at 1200 rpm for 20 minutes. Then add 6 parts of pretreated calcium sulfate whiskers and 6 parts of silane (KH570) modified flake talc powder in sequence. Use a high-shear emulsifier (10000 rpm) at 48°C for 5 minutes to form a uniform composite. S5. After cooling to 35℃, add 5 parts of epoxy siloxane curing agent (Silquest A-187), 0.5 parts of defoamer (BYK-024) and 0.6 parts of leveling agent (Tego Glide 410) simultaneously, and stir at low speed of 500rpm for 30 minutes; transfer to a vacuum reactor (-0.08MPa) for degassing for 20 minutes, and cure at 40℃ for 24 hours. Filter the material (using a 200-mesh filter) to obtain a chlorine-free rubber treatment agent for the footwear industry.

[0035] The remaining raw materials and preparation process are the same as in Example 1.

[0036] Comparative Example 1 The difference between this comparative example and Example 1 is that the EVA emulsion is not modified with a coupling agent. The specific implementation steps of S1 are as follows: S1. 20 parts of lanthanum oxide and 20 parts of cerium oxide are ball-milled and mixed, and then subjected to plasma activation treatment (inert gas atmosphere, 300W, 10 minutes) to obtain lanthanum oxide / cerium oxide composite powder; 100 parts of calcium sulfate whiskers were dried in an oven at 110°C for 2 hours, and then dissolved in an ethanol aqueous solution with 2.0 parts of stearic acid. The mixture was stirred in a water bath at 60°C until completely dissolved, filtered, heated to 90°C, stirred for 30 minutes, washed twice with hot water at 60°C, and dried with hot air at 110°C for 1 hour to obtain pretreated calcium sulfate whiskers. (The names in the remaining steps will be adjusted accordingly.) The remaining raw materials and preparation process are the same as in Example 1.

[0037] Comparative Example 2 The difference between this comparative example and Example 1 is that the calcium sulfate whiskers are not modified with stearic acid. The specific implementation steps of S1 are as follows: S1. Preheat 95 parts of EVA emulsion (ethylene vinyl acetate content 30%) to 60°C, add 5 parts of KH570, and react for 2 hours to form silane-modified EVA emulsion. 20 parts of lanthanum oxide and 20 parts of cerium oxide were ball-milled and mixed, and then subjected to plasma activation treatment (inert gas atmosphere, 300W, 10 minutes) to obtain lanthanum oxide / cerium oxide composite powder; (The names in the remaining steps will be adjusted accordingly.) The remaining raw materials and preparation process are the same as in Example 1.

[0038] Comparative Example 3 The difference between this comparative example and Example 1 is that stearic acid-modified calcium sulfate whiskers are not added. The specific implementation steps are as follows: S1. Preheat 95 parts of EVA emulsion (ethylene vinyl acetate content 30%) to 60°C, add 5 parts of KH570, and react for 2 hours to form silane-modified EVA emulsion. 20 parts of lanthanum oxide and 20 parts of cerium oxide were ball-milled and mixed, and then subjected to plasma activation treatment (inert gas atmosphere, 300W, 10 minutes) to obtain lanthanum oxide / cerium oxide composite powder; S2. Add 6 parts of lanthanum oxide / cerium oxide composite powder, 2.5 parts of zinc borate and 0.8 parts of silane coupling agent KH560 to a high-speed disperser, add 30 parts of deionized water, disperse at 3000 rpm for 15 minutes, and grind through a basket mill to prepare rare earth slurry. S3. Add 40 parts of silane (KH550) modified EVA emulsion and 18 parts of acrylate emulsion to the reactor in sequence, slowly add 1.5 parts of zirconium acetylacetonate, stir at 400 rpm, heat to 50°C and react for 30 minutes, add nonionic wetting agent TegoWet 270 to obtain polymer system. S4. Slowly add the rare earth slurry to the polymer system, stirring at 1200 rpm for 20 minutes. Add 5 parts of silane-modified flake talc powder and process with a high-shear emulsifier (10000 rpm) for 5 minutes to form a uniform composite. S5. After cooling to 35℃, add 4 parts of epoxy siloxane curing agent (Momentive Silquest A-187), 0.4 parts of defoamer (BYK-024) and 0.5 parts of leveling agent (Tego Glide 410) simultaneously, and stir at low speed of 500rpm for 30 minutes; transfer to a vacuum reactor (-0.08MPa) for degassing for 20 minutes, and cure at 40℃ for 24 hours. Filter the material (using a 200-mesh filter) to obtain a chlorine-free rubber treatment agent for the footwear industry.

[0039] The remaining raw materials and preparation process are the same as in Example 1.

[0040] Comparative Example 4 The difference between this comparative example and Example 1 is that cerium oxide is not added. The specific implementation steps of S1 are as follows: S1. Preheat 95 parts of EVA emulsion (ethylene vinyl acetate content 30%) to 60°C, add 5 parts of KH570, and react for 2 hours to form silane-modified EVA emulsion. Twenty portions of lanthanum oxide were ball-milled and then subjected to plasma activation treatment (inert gas atmosphere, 300W, 10 minutes) to obtain lanthanum oxide powder. 100 parts of calcium sulfate whiskers were dried in an oven at 110°C for 2 hours, and then dissolved in an ethanol aqueous solution with 2.0 parts of stearic acid. The mixture was stirred in a water bath at 60°C until completely dissolved, filtered, heated to 90°C, stirred for 30 minutes, washed twice with hot water at 60°C, and dried with hot air at 110°C for 1 hour to obtain pretreated calcium sulfate whiskers. (The names in the remaining steps will be adjusted accordingly.) The remaining raw materials and preparation process are the same as in Example 1.

[0041] Comparative Example 5 The difference between this comparative example and Example 1 is that lanthanum oxide / cerium oxide composite rare earth is not added. The specific implementation steps are as follows: S1. Preheat 95 parts of EVA emulsion (ethylene vinyl acetate content 30%) to 60°C, add 5 parts of KH570, and react for 2 hours to form silane-modified EVA emulsion. 100 parts of calcium sulfate whiskers were dried in an oven at 110°C for 2 hours, and then dissolved in an ethanol aqueous solution with 2.0 parts of stearic acid. The mixture was stirred in a water bath at 60°C until completely dissolved, filtered, heated to 90°C, stirred for 30 minutes, washed twice with hot water at 60°C, and dried with hot air at 110°C for 1 hour to obtain pretreated calcium sulfate whiskers. S2. Add 2.5 parts of zinc borate and 0.8 parts of silane coupling agent KH560 to a high-speed disperser, add 30 parts of deionized water, disperse at 3000 rpm for 15 minutes, and grind through a basket mill to prepare rare earth slurry. S3. Add 40 parts of silane (KH560) modified EVA emulsion and 18 parts of acrylate emulsion to the reactor in sequence, slowly add 1.5 parts of zirconium acetylacetonate, stir at 400 rpm, heat to 50°C and react for 30 minutes, add nonionic wetting agent TegoWet 270 to obtain polymer system. S4. Slowly add the rare earth slurry to the polymer system, stirring at 1200 rpm for 20 minutes. Then add 7 parts of pretreated calcium sulfate whiskers and 5 parts of silane-modified flaky talc powder in sequence. Process the mixture for 5 minutes using a high-shear emulsifier (10000 rpm) to form a uniform composite. S5. After cooling to 35℃, add 4 parts of epoxy siloxane curing agent (Momentive Silquest A-187), 0.4 parts of defoamer (BYK-024) and 0.5 parts of leveling agent (Tego Glide 410) simultaneously, and stir at low speed of 500rpm for 30 minutes; transfer to a vacuum reactor (-0.08MPa) for degassing for 20 minutes, and cure at 40℃ for 24 hours. Filter the material (using a 200-mesh filter) to obtain a chlorine-free rubber treatment agent for the footwear industry.

[0042] The remaining raw materials and preparation process are the same as in Example 1.

[0043] Performance testing (1) Initial peel strength (N / cm): GB / T 34444-2017 "Determination of interlayer peel strength of paper and paperboard" was used to test the peel strength of the chlorine-free rubber treatment agent for footwear obtained in the various embodiments and comparative examples of this application. (2) Strength retention rate (%) at 85℃ / 85%RH×7 days: The damp heat aging strength retention rate of the shoemaking chlorine-free rubber treatment agents obtained in various embodiments and comparative examples of this application was tested according to GB / T 1740-2007 "Test Method for Damp Heat Resistance of Coating Film". (3) Strength retention rate (%) after 150℃×168h: The high-temperature aging strength retention rate of the shoemaking chlorine-free rubber treatment agents obtained in various embodiments and comparative examples of this application was tested according to GB / T 1766-2008 "Rating method for aging of paint and varnish coatings". (4) Contact angle (°): The contact angle of the shoemaking chlorine-free rubber treatment agent obtained in the various embodiments and comparative examples of this application was tested according to GB / T 30693-2014 "Measurement of contact angle between plastic film and water". The results are shown in Table 1: Table 1 As shown in Table 1, the synergistic effect of the lanthanum oxide / cerium oxide composite rare earth is the core mechanism for improving the resistance to damp heat. In Examples 1-6, the strength retention rate after 7 days of damp heat aging at 85℃ / 85%RH all exceeded 92%, significantly higher than Comparative Example 4 (86.6%) without cerium oxide and Comparative Example 5 (86.7%) without rare earth elements. This confirms that the high electronegativity of lanthanum and the variable valence characteristics of cerium form a dynamic protective network: after lanthanum adsorbs water molecules, cerium... The price cycle will Free radicals are reduced to H2O, avoiding interfacial hydrolysis. This synergistic effect is more pronounced at high temperatures; in Example 1, the strength retention rate reached 90.5% after 150℃×168h, while in Comparative Example 4, the retention rate was only 79.3% because lanthanum oxide alone could not complete the free radical scavenging cycle.

[0044] The dual composite structure of stearic acid-modified calcium sulfate whiskers and silane-modified talc creates an integrated system of physical reinforcement and barrier. The peel strength of Example 1 (47.6 N / cm) is significantly improved compared with Comparative Example 2 (44.2 N / cm) without whiskers and Comparative Example 3 (40.8 N / cm) without whiskers, indicating that the long-chain alkyl group of stearic acid can reduce the surface energy of the whiskers and enhance their compatibility with the polymer matrix. Its needle-like structure inhibits resin melt flow at high temperatures. Meanwhile, the flake-like talc extends the water vapor penetration path through its directional arrangement, making the contact angle of Example 1 (101.2°) much higher than that of Comparative Example 3 (86.6°). The synergistic effect of the two increases the high-temperature retention rate at 150°C by 13.7%.

[0045] The chemical crosslinking network between the silane-modified EVA emulsion and the epoxy siloxane curing agent is crucial for ensuring interfacial adhesion. Comparative Example 1, where the EVA was not modified with KH570, showed a 6% decrease in peel strength and a 5.5% reduction in wet heat retention, confirming the dual role of the γ-siloxane side chain: on one hand, it covalently bonds with the hydroxyl groups on the rubber surface through siloxane bonds; on the other hand, it forms an interpenetrating network with the zirconium acetylacetonate-catalyzed acrylate emulsion, significantly improving interfacial bonding strength. This chemical synergy, combined with the physical reinforcement of rare earth elements and whiskers, forms a multi-level protection, enabling the examples to maintain excellent performance under multiple aging conditions, while the absence of any one of these elements leads to a precipitous decline in performance.

[0046] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.

Claims

1. A chlorine-free rubber treatment agent for the shoemaking industry, characterized in that, By weight, it includes 35-45 parts silane-modified EVA emulsion, 15-20 parts acrylate emulsion, 5-8 parts lanthanum oxide / cerium oxide composite powder, 2-3 parts zinc borate, 6-8 parts pretreated calcium sulfate whiskers, 4-6 parts silane-modified flake talc powder, 3-5 parts epoxy siloxane curing agent, 1-2 parts zirconium acetylacetonate, 0.5-1 part nonionic wetting agent, 0.3-0.5 parts defoamer, and 0.4-0.6 parts leveling agent.

2. The chlorine-free rubber treatment agent for shoemaking according to claim 1, characterized in that, The silane-modified EVA emulsion is prepared by the following steps: Preheat the EVA emulsion to 55-60℃, add KH570, and react for 2-2.5 hours to form a silane-modified EVA emulsion; The weight ratio of the EVA emulsion to KH570 is (94-96):(4-6); the content of ethylene vinyl acetate in the EVA emulsion is 28% to 33%.

3. The chlorine-free rubber treatment agent for shoemaking according to claim 1, characterized in that, The lanthanum oxide / cerium oxide composite powder is prepared by the following steps: Lanthanum oxide and cerium oxide were ball-milled and mixed, and then subjected to plasma activation treatment to obtain lanthanum oxide / cerium oxide composite powder; The weight ratio of lanthanum oxide to cerium oxide is 1:(0.9-1.1); the plasma activation treatment conditions are: under an inert gas atmosphere, a power of 290-300W for 10-12 minutes.

4. The chlorine-free rubber treatment agent for shoemaking according to claim 1, characterized in that, The pretreated calcium sulfate whiskers are obtained by the following steps: Calcium sulfate whiskers are dried in an oven at 100-110℃ for 2-2.5 hours, dissolved in an ethanol aqueous solution with stearic acid, stirred in a water bath at 55-60℃ until completely dissolved, filtered, heated to 88-92℃, stirred for 30-40 minutes, washed 2-3 times with hot water at 55-60℃, and dried with hot air at 105-110℃ for 1-1.5 hours to obtain pretreated calcium sulfate whiskers. The weight ratio of the calcium sulfate whiskers to stearic acid is 100:(1.8-2.5).

5. The chlorine-free rubber treatment agent for shoemaking according to claim 1, characterized in that, The silane in the silane-modified flake talc powder is one or a combination of KH550, KH560 and KH570.

6. A method for preparing a chlorine-free rubber treatment agent for the shoemaking industry, characterized in that, The preparation of the chlorine-free rubber treatment agent according to any one of claims 1-5 includes the following steps: S1. Lanthanum oxide / cerium oxide composite powder, zinc borate, silane coupling agent and deionized water are dispersed and ground to prepare rare earth slurry; S2. Slowly add zirconium acetylacetonate to silane-modified EVA emulsion and acrylate emulsion, stir, heat and react, add nonionic wetting agent to obtain polymer system; S3. Slowly add the rare earth slurry to the polymer system, stir, and then add pretreated calcium sulfate whiskers and silane-modified flaky talc in sequence. Emulsify to form a uniform composite. S4. After cooling to 32-35℃, add epoxy siloxane curing agent, and simultaneously add defoamer and leveling agent while stirring at low speed; defoam and cure, filter and discharge to obtain chlorine-free rubber treatment agent for the footwear industry.

7. The preparation method of a chlorine-free rubber treatment agent for shoemaking according to claim 6, characterized in that, The dispersion and grinding conditions in S1 are: stirring at 2800-3000 rpm for 15-20 minutes; the heating reaction in S2 is: heating to 45-50℃ and reacting for 30-35 minutes, with a stirring speed of 400-450 rpm.

8. The method for preparing a chlorine-free rubber treatment agent for the shoemaking industry according to claim 6, characterized in that, The emulsification conditions in S3 are: 45-50℃, 9000-10000 rpm for 5-7 minutes.

9. The method for preparing a chlorine-free rubber treatment agent for the shoemaking industry according to claim 6, characterized in that, In step S4, the degassing and maturation process involves transferring the material to a vacuum reactor and degassing it under vacuum for 20-25 minutes; then maturing it at 37-40°C for 22-24 hours; the filter screen has a pore size of 180-220 mesh.

10. The method for preparing a chlorine-free rubber treatment agent for shoemaking according to claim 6, characterized in that, The nonionic wetting agent is Tego Wet 270; the epoxy siloxane curing agent is Silquest A-187; the defoamer is BYK-024; and the leveling agent is Tego Glide 410.

Citation Information

Patent Citations

  • Yellowing-resistant polishing-free two-component rubber treating agent and using method thereof

    CN119978938A